Frailty is associated with worse cognitive functioning in older adults - Li, Chunmei; Ge, Song; Yin, Yueheng; Tian, Chong; Mei, Yongxia; Han, Peijin (Frontiers in Psychiatry, 2023)
Introduction: Frailty and impaired cognitive functioning often co-occur in older adults and are associated with adverse health outcomes. However, their relationship is unclear. This study sought to examine the association of frailty status with cognitive functioning in older adults. Method: The study population consisted of 2296 older adults aged ≥60 from the National Health and Nutrition Examination Survey 2011-2014. Frailty status was measured based on the Fried Phenotype and the participants were categorized into three groups- robust, pre-frailty, and frailty. Cognitive functioning was measured using the Consortium to Establish a Registry for Alzheimer’s Disease Word Learning subtest (CERAD-WL) immediate and delayed recall tests, the Animal Fluency test (AFT), and the Digit Symbol Substitution Test (DSST). Test-specific and global cognition z-scores were calculated. Multinomial linear regression models were constructed to examine the association between frailty status (reference: robust) and test-specific and global cognition z-scores. Multiple linear regression models were used to examine the relationship between the number of frailty dimensions and test-specific and global cognition z-scores. All models controlled for age, race/ethnicity, education, total cholesterol level, and systolic blood pressure. Results: About half of the participants (median age 68 years) were female (49.9%) and non-Hispanic White (48.7%). A quarter (23.3%) of the participants completed some college and above. Multinominal linear regression showed that compared with participants who were robust, those with frailty had worse DSST (β = -0.234, 95% confidence interval [CI]: -0.391, -0.078, P = 0.003) and global cognition z scores (β = -0.129, 95% CI -0.233, -0.025, P = 0.02). Multiple linear regression model showed that the number of frailty dimensions was significantly associated with decreased the DSST (β = -0.065, 95%CI -0.103, -0.026, P=0.001) and global cognition z-scores (β = -0.034, 95% CI -0.06, -0.009, P=0.009). Conclusions: Frailty is associated with worse processing speed, sustained attention, working memory, and global cognition in older adults. Prevention and treatment of frailty in older adults may help protect their cognitive functioning. Further, clinicians should consider assessing cognitive functioning, especially processing speed, sustained attention, and working memory, among frail older patients, which may allow early identification and interventions of cognitive impairment.